2017
DOI: 10.1098/rstb.2016.0379
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of plastid terminal oxidase in Synechocystis sp. PCC 6803 alters cellular redox state

Abstract: Cyanobacteria are the most ancient organisms performing oxygenic photosynthesis, and they are the ancestors of plant plastids. All plastids contain the plastid terminal oxidase (PTOX), while only certain cyanobacteria contain PTOX. Many putative functions have been discussed for PTOX in higher plants including a photoprotective role during abiotic stresses like high light, salinity and extreme temperatures. Since PTOX oxidizes PQH and reduces oxygen to water, it is thought to protect against photo-oxidative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…These authors found that the spectroscopic signature of charge separation in preparations of partially oxidized reaction centres was replaced by that of an energy dissipation process. Krieger-Liszkay and co-workers [10] describe how photosystem (PS) II electron transport capacity in the cyanobacterium Synechocystis sp. PCC 6803 was altered relative to PSI by constitutive expression of the plastid terminal oxidase, which oxidizes plastoquinol and reduces oxygen to water.…”
Section: Enhancing Photosynthesis In Microorganismsmentioning
confidence: 99%
“…These authors found that the spectroscopic signature of charge separation in preparations of partially oxidized reaction centres was replaced by that of an energy dissipation process. Krieger-Liszkay and co-workers [10] describe how photosystem (PS) II electron transport capacity in the cyanobacterium Synechocystis sp. PCC 6803 was altered relative to PSI by constitutive expression of the plastid terminal oxidase, which oxidizes plastoquinol and reduces oxygen to water.…”
Section: Enhancing Photosynthesis In Microorganismsmentioning
confidence: 99%
“…While over-expression of C. reinhardtii PTOX1 in plants makes the mutants more sensitive to HL than WT [38,39] and Arabidopsis PTOX in tobacco promotes oxidative stress [40,41]. Similarly, OsPTOX expression in Synechocystis did not affect growth under standard growth conditions (light intensities between 50 and 150 µmol photons m − 2 s − 1 ) [42]. In other stress treatments, over-expression of PTOX from the salt-tolerant brassica species Eutrema salsugineum show faster induction and a greater final level of PTOX activity once exposed to salt stress [43].…”
Section: Discussionmentioning
confidence: 93%
“…Such hypothesis is corroborated by the markedly upregulated protein levels of NDC1 in the plants under NH + 4 nutrition ( Figure 6B). Remarkably, PTOX is considered an important component of redox sensing in higher plants in relation to the redoxin system (Kambakam et al, 2016;Feilke et al, 2017; and references therein), which regulates several chloroplast-localized processes including PSI assembly (Zhu et al, 2016) and improves the tolerance of plants to stress (Johnson and Stepien, 2016).…”
Section: The Upregulated Cet/ndc1-ptox Pathways Under Nh + 4 Nutritiomentioning
confidence: 99%